2020
DOI: 10.1371/journal.pntd.0008281
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya outbreak (2015) in the Colombian Caribbean: Latent classes and gender differences in virus infection

Abstract: Chikungunya virus (CHIKV), a mosquito-borne alphavirus of the Togaviridae family, is part of a group of emergent diseases, including arbovirus, constituting an increasing public health problem in tropical areas worldwide. CHIKV causes a severe and debilitating disease with high morbidity. The first Colombian autochthonous case was reported in the Colombian Caribbean region in September 2014. Within the next two to three months, the CHIKV outbreak reached its peak. Although the CHIKV pattern of clinical symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Males have outnumbered females [35]. Another similar study by Oscar M. Vidal was done in 2020, in which Males were more likely to contract Dengue than females, although females were more likely to contract Сhikungunya [36]. Many recent studies reported coinfection is associated with clinically severe disease leading to high mortality compared with Mon infection [37].…”
Section: Discussionmentioning
confidence: 97%
“…Males have outnumbered females [35]. Another similar study by Oscar M. Vidal was done in 2020, in which Males were more likely to contract Dengue than females, although females were more likely to contract Сhikungunya [36]. Many recent studies reported coinfection is associated with clinically severe disease leading to high mortality compared with Mon infection [37].…”
Section: Discussionmentioning
confidence: 97%
“…Via ML, it has been possible to develop models to identify individuals more susceptible to developing common and rare diseases [ 58 , 59 , 60 , 61 , 62 , 63 , 67 , 88 , 89 , 90 , 91 , 92 , 93 ] and determine diverse phenotypic response profiles in infectious diseases [ 94 , 95 , 96 ]. Considering that ML- and computational-based models have the potential to overcome the limitations of current established clinical models for the diagnosis and follow-up of neurodegenerative diseases, including AD [ 97 ], here we studied the feasibility of ML algorithms for predicting Alzheimer’s disease age of onset (ADAOO) in individuals from the Paisa genetic isolate. We argue that these ML-based predictive models will improve our understanding of the disease and provide a more accurate and precise definition of the AD natural history landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work may include to develop ML predictive models that can classify new individuals to such derived groups (Roman, 2019). Interestingly, the combination unsupervised ML techniques may lead to the identification of individuals exhibiting differential clinical profiles (i.e., extreme phenotypes; Acosta et al, 2011;Arcos-Burgos et al, 2019;Elia et al, 2009;Pérez-Gracia et al, 2010;Vidal et al, 2020;Yu et al, 2017;Yu et al, 2018), hence contributing to the development of personalized interventions, treatments, and follow-up strategies. The combination of supervised and unsupervised ML techniques as well as the automation of the data analysis process could allow the development of data-driven Intelligent Systems supporting psychologists to make more accurate and timely decisions (de Mello & de Souza, 2019;Luxton, 2016).…”
Section: Psychology: Predictive Models Clustering and Intelligent Systemsmentioning
confidence: 99%